2020
DOI: 10.3389/fphar.2020.00621
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Anticancer Agents Used in Children: A Focus on Their Off-Label Use Through Data From the Spontaneous Reporting System

Abstract: Background: Among factors influencing the higher risk of developing unknown or rare adverse drug reactions (ADRs) among children and adolescents, there is the frequent offlabel use of drugs that seems to be very common in pediatric oncological patients. Our study aim to collect and evaluate data on the safety profile of antineoplastic drugs and their off-label use in the pediatrics population using real life data. Methods:We retrieved Individual Case Safety Reports (ICSRs) with an anticancer agent as suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
(58 reference statements)
2
8
0
Order By: Relevance
“…For both reasons, the comparison of the incidence of ADR between the use of off-label and on-label drugs was considered inappropriate. A similar trend was documented in the study of Mascolo et al, which aimed to assess off-label use of Individual Case Safety Reports concerning antineoplastic drugs in children and found that only 18 (7.6%) out of 236 were classified as off-label cases ( Mascolo et al, 2020 ). These authors considered the low number of cases were due to underreporting.…”
Section: Discussionsupporting
confidence: 73%
“…For both reasons, the comparison of the incidence of ADR between the use of off-label and on-label drugs was considered inappropriate. A similar trend was documented in the study of Mascolo et al, which aimed to assess off-label use of Individual Case Safety Reports concerning antineoplastic drugs in children and found that only 18 (7.6%) out of 236 were classified as off-label cases ( Mascolo et al, 2020 ). These authors considered the low number of cases were due to underreporting.…”
Section: Discussionsupporting
confidence: 73%
“…To the best of the author’s knowledge, this study addressed the adverse events of off-label use for the first time through AE reporting system databases in a comprehensive manner. Relatively few studies have recently described AEs associated with off-label uses in limited populations 60 or specific cases. 61 The results here can be useful when making predictions of AEs associated with off-label use.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are concerns that there is an underreporting phenomenon occurring through national spontaneous reporting systems. [ 94 ]…”
Section: Safety Initiativesmentioning
confidence: 99%